Academic Senate Minutes 2003-12-18 - Academic Senate:::::::::
Agenda and minutes approved. Chair's report. Consent items: Duties of S&F in the by-laws, Amendment to Grade Appeal Policy, Spanish Program 4 unit conversion all approved. Special Report on the financial status of the Green Music Center. Long Range Academic Plan and its relation to Strategic Plan discussion. Resolution regarding Grade Posting by PeopleSoft Software first reading waived, resolution failed. Reports from Provost, Vice President Administration and Finance, and Chair-Elect.